(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
Autores: A. Calvo Espiga y Mª A. Peñín González Editorial: Civitas y Thomson Reuters, Cizur Menor, 2010. 349 págs.